Exploring the utility of ctDNA testing in high-risk breast cancer patients in a community setting: case series - Kasen Wong; Alyssa Kameoka; Jami Aya Fukui (Therapeutic Advances in Medical Oncology)
Despite initial treatment, breast cancer recurrence affects approximately 30% of patients. Currently, there exists no standardized approach to detect recurrence before clinical or radiologic signs manifest. Circulating tumor DNA (ctDNA) is a minimally invasive blood test that offers potential to monitor molecular disease and individualize care. This study explores the utility of ctDNA in recurrence monitoring and clinical decision-making for high-risk breast cancer cases within a community setting. Seventy-two patients with high-risk breast cancer features—defined as stage III disease, triple-negative or HR−/HER2+ following neoadjuvant treatment, metastatic breast cancer without evidence of disease, bilateral breast cancer history, high-risk genetics (BRCA1/BRCA2 mutations), <40 years old at diagnosis, or history of breast cancer recurrence—were offered tumor-informed ctDNA assays at 3- to 6-month intervals. Analysis was conducted on 67 cases with a mean diagnostic age of 52.69 at diagnosis. The cohort was ethnically diverse, including White ( n  = 21, 31.82%), Japanese ( n  = 15, 22.73%), Native Hawaiian ( n  = 11, 16.67%), and Filipino ( n  = 7, 10.61%) patients. Seven (10.45%) tests were positive: six predicted recurrence despite four with initially negative radiological findings, and one prompted treatment resumption following prior non-adherence. However, one negative result was false and later showed a contralateral breast recurrence, and another negative test coincided with a new primary cholangiocarcinoma. In two cases, ctDNA negativity was utilized to monitor treatment response in metastatic disease and inform therapeutic adjustments. In real-world settings, ctDNA served as a valuable tool for earlier recurrence prediction, expediting radiological confirmation, and influencing treatment. Nevertheless, false results carry the risk of hindering effective care and inducing considerable patient anxiety. Future large-scale studies are warranted in high-risk breast cancer populations to evaluate ctDNA’s impact on patient survival outcomes, treatment monitoring, and patients’ emotional experiences.